The Role of Underflows and Weather on Sediment Distribution in Glacial-Fed Lake Linné, Svalbard, Norway, 2011 - Diana Zamora-Reyes (Arctic Data Center, 2013)
Linnévatnet (78° 2’N, 13° 49’E), is a glacial-fed lake located in Svalbard, an archipelago north of Norway. Sediments found in the lake are supplied by the Linné Glacier, 8km south of the lake, and are transported by the melt stream into the lake, creating laminations with a strong signal of seasonal deposition. Due to its immaculate environment and recent rapid increase in temperature, this site is an ideal place to study past-climate proxies and determine how the changing environment is affecting the area. The objective of this study is to determine the frequency of water underflows influencing sediment distribution and how they are related to weather patterns. Loggers recorded water temperature at 6 depths in 2 separate stations; weather was logged at an adjacent weather station. Underflow events, identified based on large changes in water temperature at the deepest loggers, were most common near the stream inflow. These events were most often correlated with changes in wind direction, wind speed and precipitation. In the future, underflows will be compared to time-lapse pictures of the lake, data of an intervalometer - which records the amount of sedimentation- and tilt data to see how lake processes affect sedimentation distribution throughout the lake.